The power of open: benefits, barriers, and strategies for integration of open educational resources. (3rd May 2020) - Luo, Tian; Hostetler, Kirsten; Freeman, Candice; Stefaniak, Jill
ABSTRACT: Open Educational Resources (OER) are becoming a significant, mission-driven trend within educational literature. To help address rising costs, instructors and designers are looking to OER to effectively replace traditional instructional content, which requires more than just identify and replace. Drawing from 51 OER studies conducted in countries across the five continents, this systematic literature review explored the empirical themes evident in the current research on a global scale. This review found (1) discoverability, sustainability, and remixing are significant barriers that stand in the way of OER disrupting traditional textbook models; (2) there is no significant difference in learning outcomes when instructors incorporate OER; and (3) implementation of OER as instructional strategies is challenging but can be effective in supporting positive learning outcomes when properly designed. The paper concludes with a discussion of gaps in the literature, considerations for implementation and further directions for future research.